Sergio Pérez Cortés, Conflits de formalisation en linguistique. Université de Paris X, Nanterre, 1983; 136 pp. - Garza Cuarón, Beatriz (El Colegio de México, 1987)
Se reseñó el libro: Conflits de formalisation en linguistique.